2021
DOI: 10.1126/scitranslmed.abe1633
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with ROS detoxifying gold quantum clusters alleviates the functional decline in a mouse model of Friedreich ataxia

Abstract: Friedreich ataxia (FRDA) is caused by the reduced expression of the mitochondrial protein frataxin (FXN) due to an intronic GAA trinucleotide repeat expansion in the FXN gene. Although FRDA has no cure and few treatment options, there is research dedicated to finding an agent that can curb disease progression and address symptoms as neurobehavioral deficits, muscle endurance, and heart contractile dysfunctions. Because oxidative stress and mitochondrial dysfunctions are implicated in FRDA, we demonstrated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 131 publications
0
13
0
Order By: Relevance
“…The gold cluster superstructures identified as Au8-pXs have been regarded as an improved derivative of gold quantum clusters, demonstrating cytoprotective properties against mesenchymal stem cells (MSCs) derived from bone marrow samples of patients with FRDA [126]. A catalytic activity of 5 to 10 µM Au8-pXs attenuated mitochondrial ROS production and increased the protein level of frataxin, resulting in restoration of mitochondrial function and bioenergetic capacity, ATP level, ETC function and MMP dissipation.…”
Section: Exenatidementioning
confidence: 99%
See 2 more Smart Citations
“…The gold cluster superstructures identified as Au8-pXs have been regarded as an improved derivative of gold quantum clusters, demonstrating cytoprotective properties against mesenchymal stem cells (MSCs) derived from bone marrow samples of patients with FRDA [126]. A catalytic activity of 5 to 10 µM Au8-pXs attenuated mitochondrial ROS production and increased the protein level of frataxin, resulting in restoration of mitochondrial function and bioenergetic capacity, ATP level, ETC function and MMP dissipation.…”
Section: Exenatidementioning
confidence: 99%
“…In addition, systemic injection of 10 µM Au8-pXs in the YG8sR mice has been shown to improve motor deficits and neuromuscular function assessed by rotarod and footprint tests, and treadmill and forelimb grip tests, respectively, and cardiac contractility. Villa et al [126] observed that matrix metalloproteinase (MMP9) deficiency reduced collagen deposition in the skeletal muscle and cardiac fibrosis, concomitant with a decrease in tumor necrosis receptor-associated factor 6 (TRAF6) and collagen synthesis, regulating myocardial necroptosis and remodeling.…”
Section: Exenatidementioning
confidence: 99%
See 1 more Smart Citation
“…Understanding how these compounds are working and discovering multiple pathways to increase Fxn levels may provide a multipronged approach to effective therapies for FRDA. Indeed, a recent study suggests that buffering the oxidative stress associated with FRDA using gold quantum cluster therapy reduced ROS, decreased autophagy, and increased Fxn protein expression providing a novel therapeutic strategy to delay disease progression in FRDA ( 73 ). This study along with others and our work reported here suggests that there may be novel therapeutic approaches to reduce disease progression in FRDA.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of cytosolic superoxide dismutase 1 (SOD1) and mitochondrial superoxide dismutase 2 (SOD2) was measured on 10 μg proteins of the respective extracts, obtained as indicated above, in 100 μl PBS containing 50 μM xanthine, 5 U/ml xanthine oxidase, 1 μg/ml oxidized cytochrome c. The rate of cytochrome c reduction, which is inhibited by SOD, was monitored for 5 minutes by reading the absorbance at 550 nm with a Synergy HT Multi-Detection Microplate Reader (Bio-Tek Instruments). Results were expressed as μmoles reduced cytochrome c/min/mg cytosolic or mitochondrial proteins [29]. Catalase and glutathione peroxidase (GPX) were measured on whole cell lysates using the Catalase Activity Assay Kit (Colorimetric/Fluorometric) (Abcam) and the Glutathione Peroxidase Assay Kit (Colorimetric) (Abcam), as per manufacturer's instructions.…”
Section: Antioxidant Enzymes Activitymentioning
confidence: 99%